(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
To estimate the patient’s antihypertensive medication knowledge from south Indian population. Five hundred (500) patients were participated in this study. Out of 500, 46 patients were pre hypertensive so 456 patients were interviewed using a questionnaire which captured data on patient’s medication knowledge at south Indian private hospitals in Tamilnadu, India. The present study consists 4 visits that include, screening visit, follow up visit-1 to follow up visit-3. The study measure the knowledge of drug level between usual care and pharmaceutical care. Usual care patients were not educated whereas pharmaceutical care patients were educated by principal researcher. Out of 500 patients, males (49.29 ± 6.5) and females (50.63 ± 6.5) participated in the study. Knowledge of medication and compliance are important in drug treatment regimens. In usual care, Out of 500 patients 65% of patients reported that they were aware that they were taking drugs for high blood pressure where as 35% were not. 32% of patients were able to tell the name of the drugs whereas 68% were not. 64% of the people were thinking it’s no cure for hypertension and only 36% of the people feel that it’s curable. 64% of the people said lifelong and only 36% of subjects said they are taking only for short term treatment of hypertension. 66% of the people have no clue and knowledge about the side effects of antihypertensive medicines where as 34% were aware, 33% were shared if they take any other drugs along with antihypertensive drugs where as 67% were not, 70% of the patients did not inform to the pharmacist about their high blood pressure (HBP) tablet intake while purchasing other medicines whereas 30% informed. However medication knowledge was improved after the pharmaceutical care.